RF Transimpedance Amplifier for CATV Applications over PON - Royo, Guillermo; Sánchez-Azqueta, Carlos; Aldea, Concepción; Celma, Santiago (Jornada de Jóvenes Investigadores del I3A, 2017)
In this work, we present a fully differential transimpedance amplifier (TIA) with controllable transimpedance for use in RF overlay downstream communication systems. The transimpedance amplifier has been designed in a standard 180-nm CMOS technology and it is intended for 47 MHz to 870 MHz subcarrier multiplexed RF signals. It performs a 18 dBΩ transimpedance gain control range for extended optical input range from -6 dBm up to +2 dBm.